Central Haemangioma (Intraosseous) of Jaw - Shukla, Samarth; Acharya, Sourya; Bhola, Nitin; Chaudhary, Minul; Borle, Mr.; Grover, Mrs (Journal of Medicine, 2012)
Vascular neoplasms are common but are often much debated and discussed out entities. These mesenchymal neoplasms are categorized as benign (haemangiomas) or of intermediate behavior (heamangiopericytoma, Hemangioendotheliomas) and malignant as in Angiosarcoma and Kaposis sarcoma. But even the most benign of entities like haemngiomas can often behave in a nasty way depending on the presentation. Posing great diagnostic dilemma and management delay, we present a rare case of a young boy presenting with an ever increasing firm nodular growth in the outer left mandible. The gingival and the outer skin was intact. Xray suggested of a cystic multiloculated lesion. Biopsy on histopathology revealed an intraosseous haemngioma. A true rarity in itself with extreme paucity of such reported lesions. Again the origins and the cell of origin of haemngiomas have been at major flashpoints and cross firing especially when taken up as differentials with arteriovenous malformations. DOI: http://dx.doi.org/10.3329/jom.v13i2.12762 J Medicine 2012; 13 : 222-226